ANALISIS IMPLEMENTASI KEBIJAKAN PROGRAM DAERAH PEMBERDAYAAN MASYARAKAT (PDPM) KECAMATAN PALU TIMUR DI KOTA PALU - Nirwana, Nirwana (Katalogis, 2013)
This research aims to analyze the policy implementation the mayor of City Regulation Number 11, 2011 about teh Guideline of Society Empowerment Regional Program of East Palu Sub-istrict Palu City, This Researcah employed equality method. It was carried out in Tondo and Talise. East Palu Sub-district. The Informants of this research were bureucrac staff, local people, and the elderly people. Technique of ata collection was observation, interview, and library study. The research result shows that commnucation between the office and stakeholders in implementation the policy was not effective, In addition the resourches of the program Implementation had enaught quality. Dispotition and bureaucracy Structure of the proram implementation were important to was urgent to increase society capasity, not get for individuals but also for groups to solve problems for increasing life quality, self – creativity, an properity. Therefore, increasing the effectiveness quality of the city chief regulation policy implementation was actually supported by the four faktors mentioned above.